A study on the factors that affect the awareness on environmental issues among students in Faculty of Technology Management and Technopreneurship: a case study at UTeM City Campus / Asfarina Izni Azlan and Umi Norainshah Abdul Rani - Azlan, Asfarina Izni; Abdul Rani, Umi Norainshah (Faculty of Administrative Science and Policy Studies, 2014)
The study seeks to determine the possible factors that affect the awareness among students in Faculty of Technology Management and Technopreneurship, UTeM City Campus. A sample of 270 out of 879 students in this faculty had been selected for this study. The findings also showed that the independent variables or factors that support our hypothesis are mass media, non governmental organization roles, parental guidance and governmental roles, in which only three variables have significant correlation with the dependent variable, is the awareness on environmental issues. Thus, the factors that affect the awareness among students in Faculty of Technology Management and Technopreneurship on environmental issues are mass media, parental guidance and non governmental organization roles.